1992
DOI: 10.1042/bj2810325
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of rap1 protein in the regulation of human platelet Ca2+ fluxes

Abstract: The relationship between the 22-24 kDa cyclic AMP (cAMP)-dependent phosphoprotein previously described as being involved in the regulation of human platelet membrane Ca2+ transport and a GTP-binding protein of low molecular mass (ras-like protein) was investigated. After isolation of plasma membranes and intracellular membranes, it was found that guanosine 5'-[y-thio]triphosphate (GTP[S]) bound to plasma membrane proteins ranging in molecular mass from 22 to 29 kDa, but not to intracellular membranes. The majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…These findings are in correspondence with the hypothesis that Rap1 is a molecular "switch" that regulates SERCA activity: the cAMP-induced Rap1 activation is correlated with the inhibition of SERCA and a rise in [Ca 2ϩ ] i (present data), and the PKA-mediated phosphorylation of Rap1 relieves the inhibition, resulting in activation of Ca 2ϩ -ATPases and a decrease in [Ca 2ϩ ] i . 10,11 The latter property is also observed in Ca 2ϩ regulation by phospholamban in cardiac and muscle cells. 23,24 Phosphorylation of this 24-kDa protein by PKA triggers stimulation of cardiac sarcoplasmic reticulum Ca 2ϩ -ATPases, leading to a fall in [Ca 2ϩ ] i .…”
Section: Camp-induced Rap1 Activation Is Not Accompanied By Phosphorymentioning
confidence: 75%
See 2 more Smart Citations
“…These findings are in correspondence with the hypothesis that Rap1 is a molecular "switch" that regulates SERCA activity: the cAMP-induced Rap1 activation is correlated with the inhibition of SERCA and a rise in [Ca 2ϩ ] i (present data), and the PKA-mediated phosphorylation of Rap1 relieves the inhibition, resulting in activation of Ca 2ϩ -ATPases and a decrease in [Ca 2ϩ ] i . 10,11 The latter property is also observed in Ca 2ϩ regulation by phospholamban in cardiac and muscle cells. 23,24 Phosphorylation of this 24-kDa protein by PKA triggers stimulation of cardiac sarcoplasmic reticulum Ca 2ϩ -ATPases, leading to a fall in [Ca 2ϩ ] i .…”
Section: Camp-induced Rap1 Activation Is Not Accompanied By Phosphorymentioning
confidence: 75%
“…Two types of cAMP GEF for Rap1 have been reported: cAMP-GEF-I, also called exchange protein, directly activated by cAMP (Epac), and cAMP-GEF-II. Interestingly, earlier work by Corvazier et al 11 and LacabaratzPorret et al 10 indicated that Rap1 might be involved in Ca 2ϩ regulation in platelets. First, proteins in crude platelet plasma membrane vesicles, ranging in molecular mass from 22 to 29 kDa, bound GTP␥S.…”
Section: Camp-induced Rap1 Activation Is Not Accompanied By Phosphorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, Tao and colleagues [12] have previously suggested that PKC may affect SERCA indirectly via phosphorylation of Rap1b. Given that PKC has been shown to phosphorylate and activate Rap1b [48,49] and that phosphorylation of Rap1b by other kinases is thought to regulate SERCA activity in platelets [50][51][52], Rap1b may be involved in the regulation of SERCA activity by PKC. Further studies investigating the phosphorylation of SERCA and association of Rap1b with SERCA may help distinguish between these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…In neutrophils, in which rap1 is located primarily on the specific granules, studies suggest that it plays a crucial role in phagocytosis (Maridonneau-Parini and de Gunzburg 1992). In platelets it has been linked to cytoskeletal reorganization (Fischer et al 1990), Ca 2 ϩ regulation (Corvazier et al 1992), and to regulation of PLC ␥ activity (Torti and Lapetina 1992).…”
mentioning
confidence: 99%